2020
DOI: 10.1155/2020/8894639
|View full text |Cite
|
Sign up to set email alerts
|

Forest Loss and Susceptible Area Prediction at Sefwi Wiawso District (SWD), Ghana

Abstract: Forests provide immeasurable merits for the economies of most developing countries. Forests in developing countries experience harmful human-induced impacts such as unregulated removal of biodiversity and unsustainable land conversion. The Sefwi Wiawso District (SWD) located in Ghana, which includes portions of six protected forest reserves (FRs) such as Muro, Tano Suhien, Tano Suraw, Suhuma, Sui River, and Krokosua, is the subject of this study. The impacts of selected spatial variables on forest losses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Women harvest non-timber forest products from the CREMA to support their household food basket. This is in tandem with the burgeoning literature on the contribution of CREMAs and protected areas to livelihoods in local communities (Abukari and Mwalyosi, 2018;Islam et al, 2019;Kamwi et al, 2020;Osei-Wusu et al, 2020). The shea for instance has been heavily depended upon by the majority of the women in the CREMA Communities for income.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Women harvest non-timber forest products from the CREMA to support their household food basket. This is in tandem with the burgeoning literature on the contribution of CREMAs and protected areas to livelihoods in local communities (Abukari and Mwalyosi, 2018;Islam et al, 2019;Kamwi et al, 2020;Osei-Wusu et al, 2020). The shea for instance has been heavily depended upon by the majority of the women in the CREMA Communities for income.…”
Section: Discussionmentioning
confidence: 82%
“…Besides, other human-induced factors such as the conversion of forest landscapes into farmlands and settlements are highlighted (Osei-Wusu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, Koranteng and Zawila-Niedzwiecki [18] also noted that forest loss was a major issue in the Region, which is the most forested in Ghana. Osei-Wusu et al [61] reported remarkable conversions of protected forests to other land uses in the Sefwi Wiaso District in the new Western North Region. They also projected that 877.38 ha of close forest resources were likely to be transformed to open forests and other non-forest land cover.…”
Section: Changes In Forest Land Covermentioning
confidence: 99%
“…Global climate change causes prolonged drought, one of the triggering factors for land and forest fres [38]. Burning forests and lands results in adverse efects such as loss of biodiversity, unpredictable climatic conditions, and destruction of terrestrial biodiversity ecosystems [39,40]. Fires often occur in peat areas because peat when dry conditions reduce groundwater, making it more easily burned.…”
Section: Introductionmentioning
confidence: 99%